Variations in Challenges and Practices of Elementary School Teachers in Strengthening Cultural and Civic Literacy in Sumedang Regency - Widianti, Tira; Heryani, Rina (International Conference on Elementary Education, 2025)
The rapid advance of globalization has compelled elementary school teachers to continuously adapt to diverse challenges in fostering cultural and civic literacy. This study aims to map the variation of challenges and teaching practices among elementary teachers in Sumedang Regency, focusing on territorial characteristics. Employing an explanatory sequential mixed-method design, the research integrates quantitative data from Likert-scale surveys and qualitative insights from thematic analysis of open-ended responses, collected from 40 teachers in urban, rural, and suburban schools with varying teaching experience. Statistical and thematic analyses reveal notable differences in both the challenges and strategies encountered, influenced by school location and professional seniority. Teachers in urban schools and those with seniority reported greater complexity but demonstrated greater innovation, while teachers in rural and suburban settings faced more limitations in contextual cultural materials, digital access, and parental engagement. Novice teachers expressed a significant need for structured training and school support. Qualitative results highlight key barriers: inadequate cultural materials, limited professional development, diminished student motivation, and time constraints. These findings underscore the imperative for locally grounded resource development and professional training tailored to both territorial and experiential needs to effectively improve cultural and civic literacy at the primary level.